Silica-gel-supported Ce(SO4)2·4H2O-mediated cyclization of 2′-amino and 2′-hydroxychalcones under solvent-free conditions. Issue 1 (2nd January 2017) - Liu, Ruihuan; Zhang, Yan; Xu, Kangping; Tan, Guishan
ABSTRACT: A simple, efficient, and environmentally friendly approach for the synthesis of flavones, aza -flavones, and aza -flavanones from corresponding 2′-hydroxy or 2′-aminochalcones has been developed. The reactions are successfully conducted in presence of silica-gel-supported Ce(SO4 )2 ·4H2 O under solvent-free conditions. GRAPHICAL ABSTRACT: